Experience capitalization - training, teaching and practising it in Berlin - Moumouni, Ismail M. (Technical Centre for Agricultural and Rural Cooperation, 2019)
As an education and training institution, the experience capitalization institutionalization strategy of the Advanced Training Centre for Agriculture (CePeSa) covers three aspects: including experience capitalization modules in the training curricula; including training on capitalization in our portfolio of fee-based short-term training services for agricultural development workers; and implementing processes to capitalise the relevant experiences of the centre. The capacity to adapt training modules and methods is crucial for meeting the needs of different target groups and client organisations.